Bias-Free Language: LGBTQ + Clients and the New APA Manual. Issue 1 (1st February 2021) - Noble, Nicole; Bradley, Loretta; Hendricks, Bret
Abstract: The Publication Manual of the American Psychological Association (7th edition) contains significant new information about bias-free language to which scholars must now adhere. Consequently, these changes provide unprecedented support for the lesbian, gay, bisexual, transgender, and queer (LGBTQ+) community as the bias-free language is adopted. This article identifies resources that counseling practitioners can use to advocate for and counsel LGBTQ+ clients. Further, this article describes the significant advancements gained in gender and sexual orientation bias-free language in the 7th edition of the APA Publication Manual updates as contrasted with the 6th edition. Implications for counseling practitioners and researchers are provided.